(3GdQMeI aj GdWH hGdMceIs - (3GdegLej, Gdjefj, GdebQF, egOj Hf Ydj Hf EHQGgje, J(B815(3g`s
(3ChdgG (B:s
(3CeG HYO aEfj SejJ gPG GdcJGH cJGH GdQMeI hGdMceI hbUOJ HPdc hLg Gddg YR hLd GdcQje GdYXjes
(3BNQgG (B:s
(3fGbU GdBNQ, hjfJgj YfO bhdg(B: (3aj GdMGdjf GdMUGI gh SOI YXjeI aj GdbVjH JefY GdHhd Cf jNQL QCSG QHeG gdc GdEfSGf ef Pdc, SHHg Ccd GdMHhHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 3 / 925s
(3cTa GdWfhf(B: 2 / 836s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs